Efficacy and Safety of Minimally Invasive Percutaneous Ilio-Sacral Fixation Technique for Sacral Fractures in The Initial Twenty Cases at Department of Neurosurgery in Alexandria University. - Abdelrahman Magdy Elhabashy, MD. (Egyptian Spine Association, 2020)
Background Data: Sacral fractures constitute a major entity of pelvic fractures. 50% of these sacral fractures are not recognized on initial physical examination of the traumatized patients. The most important prognostic factor in management of sacral fractures is the presence or absence of neurological deficit. Some studies adopt the concern regarding fixation of sacral fractures in poly-traumatized patients to avoid systemic effects and complications of recumbency. Purpose: Evaluation of the efficacy and safety of the minimally invasive percutaneous ilio-sacral fixation technique in management of initial twenty cases of sacral fractures at department of Neurosurgery in Alexandria University. Study Design: Retrospective clinical case cohort study. Patients and Methods: Between March 2017 and January 2019; 20 patients were presented at Neurosurgery Department in Alexandria University hospitals with traumatic sacral fractures. They were 13 males and 7 females with the mean of 34 years (ranged from 18-55 years). Plain X ray of pelvis including antero-posterior, inlet and outlet views of pelvis, CT scan with 3D reconstructions were done. We used Dennis classification and Roy-Camille classification in our study. Stabilization of sacral fracture was done percutaneously using 7 mm cannulated partially threaded ilio-sacral screws. Clinical, neurologic and radiographic examinations were performed in the follow up period (6 months) to assess healing, evaluate clinical improvement and to detect any implant changes. Results: Total 39 percutaneous ilio-sacral screws were placed in 20 patients. Partially threaded cancellous 7.0-millimeter cannulated screws were used. Fifteen patients had unilateral double screws; one patient had unilateral triple screws; two patients had bilateral single screws for bilateral sacral fracture and two patients had unilateral single screw. Two Misplaced screws out of thirty-nine screws were found in the post-operative CT. One patient developed post-operative foot drop. All fractures healed clinically and radio-graphically except one case fixed by single screw and did not show radiological healing. Conclusion: Percutaneous ilio-sacral fixation for sacral fractures is a safe minimally invasive method for management of sacral fractures. It is effective regarding pain relief with high fusion rate. It needs a long learning curve. Single screw fixation is not a rigid fixation and may lead to hardware failure. (2019ESJ193)